Aggregation-induced emission (AIE) nanoparticles based on γ-cyclodextrin and their applications in biomedicine. (15th December 2022) - Guan, Lianxiong; Zeng, Zhi; Liu, Wei; Wang, Tengfei; Tian, Shiyao; Hu, Sheng; Tian, Dating
Abstract: Amphiphilic AIE nanoparticles (CD-TPE) were obtained by linking γ-cyclodextrin (γ-CD) and 1, 2-diphenyl-1, 2-( p -hydroxyphenyl)-ethylene (OH-TPE-OH) by an esterification reaction using hexamethylene diisocyanate (HMDI) in a one-step process. The CD-TPE was characterized by FTIR, 13 C NMR, DSC, XRD, particle size analysis, TEM, and FL. The obtained CD-TPE had good water dispersibility and could self-assemble into AIE nanoparticles. The large cavity of CD-TPE provided convenient conditions for the loading of doxorubicin (DOX) and slow-release DOX with the loading and release rates of 67.4 % and 71.3 % (pH = 5.4), respectively. The DOX release kinetic model was suitable for the Bhaskar model. Cytotoxicity analysis and cell imaging of CD-TPE were performed, showing that CD-TPE has good biocompatibility and excellent cell imaging performance. Moreover, both in vitro and in vivo antitumor experiments showed that CD-TPE has promising applications in drug delivery.